Effect of reciprocating instrumentation on chlorhexidine substantivity on human dentin: chemical analysis followed by confocal laser microscopy - Matheus Albino Souza; Fernanda Duda Bonatto; Afonso Cristiano Fleck da Silva; Ezequiel Santin Gabrielli; Felipe Trentin Motter; Larissa Piuco; Karen Barea de Paula Duarte; Charise Dallazem Bertol; Luciana Grazziotin Rossato-Grando; Carlo Theodoro Raimundy Lago; Doglas Cecchin; Juliane Bervian; et al. (Bioscience Journal, 2021)
The present research analyzed the reciprocating instrumentation associated to chlorhexidine (CHX) substantivity as its correlation with E. faecalis viability in ex vivo root canals. Eighty extracted single-rooted human teeth were used, being 40 to high-performance liquid chromatography (HPLC) and 40 to confocal laser scanning microscopy (CLSM). In both, teeth were decoronated and the cervical third was prepared. In the CLSM analysis, the root canals were inoculated with E. faecalis for 14 days. Samples were divided into 4 groups (n=10) according to instrumentation technique: no instrumentation and irrigation with distilled water (control); manual instrumentation (K-File); rotary instrumentation (ProTaper Next); and reciprocating instrumentation (Reciproc R25). Two percent chlorhexidine was applied as irrigating substance in experimental groups. Longitudinal grooves resulted in 2 halves root and 20 proof bodies in each group. Samples were divided by chance in two groups (n=10) and the outcomes were evaluated after two days and one week. The retained chlorhexidine and live cells after instrumentation techniques in each evaluation time was measured by HPLC and CLSM, respectively. Specific analysis was applied for experimental tests (p≤0.05). Both rotary as well as reciprocating techniques significantly reduced the amount of chlorhexidine on dentin in all observation periods (p<0.05). After evaluation times, all experimental groups presented lower live cells compared to control, but without statistically difference. Intragroup comparisons in times of evaluation showed no differences in instrumentation techniques, in chlorhexidine retention and number of live cells (p>0.05). Reciprocating instrumentation does not interfere on chlorhexidine substantivity.